New insights into the genetic diversity of Schistosoma mansoni and S. haematobium in Yemen - Hany, Sady; Hesham M., Al-Mekhlafi; Bonnie L., Webster; Romano, Ngui; Wahib M., Atroosh; Ahmed K., Al-Delaimy; Nabil A., Nasr; Kek, Heng Chua; Yvonne Ai, Lian Lim; Johari, Surin (BioMed Central Ltd., 2015)
Background: Human schistosomiasis is a neglected tropical disease of great importance that remains highly prevalent in Yemen, especially amongst rural communities. In order to investigate the genetic diversity of human Schistosoma species, a DNA barcoding study was conducted on S. mansoni and S. haematobium in Yemen. Methods: A cross-sectional study was conducted to collect urine and faecal samples from 400 children from five provinces in Yemen. The samples were examined for the presence of Schistosoma eggs. A partial fragment of the schistosome cox1 mitochondrial gene was analysed from each individual sample to evaluate the genetic diversity of the S. mansoni and S. haematobium infections. The data was also analysed together with previous published cox1 data for S. mansoni and S. haematobium from Africa and the Indian Ocean Islands. Results: Overall, 31.8 % of participants were found to be excreting schistosome eggs in either the urine or faeces (8.0 % S. mansoni and 22.5 % S. haematobium). Nineteen unique haplotypes of S. mansoni were detected and split into four lineages. Furthermore, nine unique haplotypes of S. haematobium were identified that could be split into two distinct groups. Conclusion: This study provides novel and interesting insights into the population diversity and structure of S. mansoni and S. haematobium in Yemen. The data adds to our understanding of the evolutionary history and phylogeography of these devastating parasites whilst the genetic information could support the control and monitoring of urogenital and intestinal schistosomiasis in these endemic areas.